Assesment Of 2012 National Health System (Skn) Detection and Curative Respond Capabilities (Covid-19 Case Study) - Rendy Setya Wardana; Isroil Samihardjo; Ede Surya Darmawan (Syntax Corporation, 2023)
Covid-19 is a new emerging disease that spreads at Indonesia in 2020. The 2012 SKN as a legislative tool that applies and plays a role in health development aims to achieve the highest level of human health in Indonesia. However, the Covid-19 pandemic has proven that the health development that has been carried out has not been able to overcome the threat of the SARS-CoV-2 virus. This is evidenced by the large number of fatalities experienced by the people of Indonesia due to infection with the SARS-CoV-2 virus. The outbreak of Covid-19 was followed by large fatalities due to massive SARS-CoV-2 virus infection throughout 2020 until early 2022. The introduction of the disease that has occurred for 2 years should have been able to be anticipated by SKN through the capabilities of the SKN component regarding efforts to detect SARS-CoV-2. CoV-2 and curative efforts against Covid-19 patients. So in this study, an effort to compare the ability of the SKN response was carried out regarding detection and curative efforts in the first year of the pandemic and the second year of the pandemic. The comparison was carried out to see how the different SKN responses to the ongoing pandemic. The results are only testing indicators on detection capabilities that have good readiness (quantity refers to the standard), while other indicators such as surveillance, hospital capacity and health workers are still in an inadequate situation. So it is necessary to strengthen the SKN in an effort to anticipate the threat of a pandemic in the future